Acceleration patterns of the head and pelvis when walking are associated with risk of falling in community-dwelling older people - Menz, Hylton B; Lord, Stephen R; Fitzpatrick, Richard C (The journals of gerontology. Series A, Biological sciences and medical sciences, 2003)
A large proportion of falls in older people occur when walking, however the mechanisms underlying impaired balance during gait are poorly understood. This study evaluated acceleration patterns of the head and pelvis when walking on a level and an unpredictably irregular surface to determine whether older people at risk of falling demonstrate an impaired ability to stabilize the body under challenging conditions. One hundred community-dwelling older people aged between 75 and 93 years were evaluated for their risk of falling using a range of physiological tests previously found to be accurate predictors of falling in prospective studies. Temporo-spatial gait parameters and acceleration patterns at the head and pelvis were then measured in three orthogonal planes while subjects walked on a flat corridor and an unpredictably irregular walkway. Harmonic ratios of head and pelvis accelerations in each plane were calculated to provide an indicator of stability. Subjects with a high risk of falling exhibited reduced temporo-spatial gait parameters and increased step timing variability. Harmonic ratios of acceleration patterns were reduced at the head and pelvis in the vertical and antero-posterior directions. These differences were particularly evident when walking on the irregular surface. Older people at risk of falling adopt a more conservative basic walking pattern, but this does not ensure that the movements of the head and pelvis are stable. The irregular pelvis and head accelerations evident in the high risk group suggests that these subjects may have difficulty controlling trunk motion and maintaining a stable visual field when walking, particularly on irregular terrain.